Pengaruh Persepsi Kualitas Produk, Online Customer Review dan Online Customer Rating Terhadap Minat Beli Konsumen pada Skincare Daviena di E-Commerce Tiktok Shop - Minarti, Tria; Sarah, Siti (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Because of new technologies, especially online shopping, customers are changing how they shop. TikTok Shop is a very popular platform in Indonesia because it is easy to use. But to keep customers buying, TikTok Shop needs to keep making its services and product quality better, especially as more companies compete for customers. This study uses descriptive and verification methods and takes a quantitative approach. The results show that how consumers judge product quality has a positive and important effect on whether they plan to buy something, both on its own and as a whole. To get more people interested in Daviena Skincare on TikTok Shop and to build trust and loyalty, it’s important to make the product quality better, get people to write good reviews, and talk to customers in the comments.